2012
DOI: 10.1038/onc.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Tumor angiogenesis is enforced by autocrine regulation of high-mobility group box 1

Abstract: The endothelium plays a pivotal role in the progression of solid tumors and is considered a highly relevant target for therapy. However, it emerges that current clinical angiogenesis inhibitors that act through inhibition of tumor-derived growth factors are prone to inducing drug resistance. Therefore, markers of tumor endothelial cells (ECs) themselves provide attractive novel therapeutic targets. In a screen for markers of tumor angiogenesis, we recently identified high-mobility group box 1 (HMGB1), known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
142
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 46 publications
(65 reference statements)
4
142
0
Order By: Relevance
“…With regards to angiogenesis, HMGB1 promotes tissue angiogenesis by increasing the production of proangiogenic cytokines including VEGF, TNF-α, and IL-8 from endothelial cells and macrophages. 34,35) DPP4, a type of peptidase and one of the therapeutic targets for DM, reportedly degrades and inactivates not only incretin hormones but also other substances, including SDF-1, BNP, and substance P. 19) Because HMGB1 has a component of partial DPP4 cleavage sites, 20) it can also be degraded and inactivated by DPP4 in vivo. Straino, et al reported that HMGB1 levels of mice skin tissue were decreased in the diabetic state, and HMGB1 application to skin wounds promoted the tissue angiogenesis and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to angiogenesis, HMGB1 promotes tissue angiogenesis by increasing the production of proangiogenic cytokines including VEGF, TNF-α, and IL-8 from endothelial cells and macrophages. 34,35) DPP4, a type of peptidase and one of the therapeutic targets for DM, reportedly degrades and inactivates not only incretin hormones but also other substances, including SDF-1, BNP, and substance P. 19) Because HMGB1 has a component of partial DPP4 cleavage sites, 20) it can also be degraded and inactivated by DPP4 in vivo. Straino, et al reported that HMGB1 levels of mice skin tissue were decreased in the diabetic state, and HMGB1 application to skin wounds promoted the tissue angiogenesis and wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] HMGB1 regulates transcription factors but also behaves as a proinflammatory cytokine mediating inflammation. 13,[15][16][17][18] Nonprotein DAMPs, including DNA, RNA, and ATP, are also released by damaged or dying cells. 6,7,19 DAMPs are associated with acute inflammatory responses, chronic inflammation, and wound healing, but are also important components of the disordered tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…HMGB1 was reported to have a potential role in the regulation of cancer autophagy and apoptosis as response to the administration of anti-cancer agent [42] as well as to regulate migration and sprouting of endothelial cells as angiogenesis in tumor progression [35]. Moreover, the blockade of its receptor resulted in suppression of tumor growth and metastasis [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that HMGB1 is one of the key modulators of tumor development and its receptor, the receptor for advanced glycation end products (RAGE) [55] or Toll Like Receptor4 (TLR4) [35], is expressed on variety of cancer cells [66][67][68][69] including colon cancer [69]. HMGB1 was reported to have a potential role in the regulation of cancer autophagy and apoptosis as response to the administration of anti-cancer agent [42] as well as to regulate migration and sprouting of endothelial cells as angiogenesis in tumor progression [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation